Analisis Gerakan tendangan sabit pada cabang olahraga pencak silat - Heri Wahyudi, (Ilmu Keolahragaan, 2012)
Abstract : Factors that affect the martial in execute hook kick in order to obtain maximal speed. The speed of kick technique, agility, also concentration degree affect this speed. One of the factor that lack of attention in execute hook kick is the angle of kick, body declivity and front knee. Coordination between basic technique and angle of kick must get attention, since those movement is simultaneous kick. Formulation of the problem posed in this study were: (1) What is the magnitude of the body segment angle and rotation angle sweeping crescent kick that produce energy, style, and speed of crescent kicks to the fighter category greatest heights high? (2) What is the magnitude of the body segment angle and rotation angle sweeping crescent kick that produce energy, style, and speed of crescent kicks greatest fighter category at low heights? Purpose of this study were (1) Determine measurement analysis of the body segment angles, speed, energy, great style kicks, crescent kicks sweep angle of rotation in sports martial arts categories of high stature. (2) Determine the results of measurement analysis of body segment angles, speed, power, great style kicks, crescent kicks sweep angle of rotation in sports martial arts categories of low height. Method that used in these research is descriptive analysis, that is analyse and serve fact sistmatically until easier to understanding and conclude. These research helped by dartfish program, that a software that essentially needed by someone in measure something that can not by eyes. For this research using dartfish with analyzer facility so that can analyze other movement that seen from the body segment angle, movement line, speed, time, also movement. Conclusions from this research is Based on the category of high stature, at an angle of 103.5 0 ≥ crescent kick and corner kick crescent sweep rotation ≤ 150.62 0 to generate the energy, style, and speed of most large crescent kick and quickly and to produce a significant backlash . Under the category of low height, on the corner of crescent kicks 0 ≤ 119.24 and rotation angle sweep of crescent kicks 0 ≤ 163.88 that produce energy, style, and speed of most large crescent kick and quickly and to produce a significant backlash.